Influences of Turnover, Retention, and Job Embeddedness in the Nursing Workforce Literature - Susan Louisa Adams (Rural Nurse Organization; Binghamton University, 2016)
Abstract Examining literature related to nursing turnover, retention and job embeddedness has implications applicable to employer and patients.  Turnover is expensive and can lead to adverse patient outcomes and few studies focus on rural nurses.  Keywords of nurse, rural, turnover, retention, and job embeddedness entered into three search engines produced 39 references from 1995-2015.  Predominance of convenience samples, lack of discussion ofreliability and validity information, and lack of theoretical or conceptual frameworks accompanied by lack of studies focused on rural nursing highlight the gaps in knowledge regarding what keeps nurses in their jobs.  Keywords: nurse, rural, turnover, retention, job embeddedness